Silent cerebral emboli following percutaneous closure of atrial septal defect in pediatric patients: a diffusion-weighted MRI study - Gonca Koç; Abdullah Özyurt; Selim Doğanay; Ali Baykan; S. Burcu Görkem; M. Sait Doğan; Özge Pamukçu; Kazım Üzüm; Abdulhakim Coşkun; Nazmi Narin (Diagnostic and Interventional Radiology, 2016)

(untitled)
PURPOSEThe aim of this prospective study was to investigate the incidence of silent cerebrovascular embolic events associated with percutaneous closure of atrial septal defect (ASD) in pediatric patients.METHODSA total of 23 consecutive pediatric patients (mean age, 10.4±3.8 years; range, 4–17 years) admitted for transcatheter closure of ASD were recruited in the study. The patients were scanned with a 1.5 Tesla clinical scanner. Two cranial magnetic resonance imaging (MRI) examinations were acquired before the procedure and within 24 hours following the catheterization. MRI included turbo spin-echo fluid-attenuated inversion recovery (FLAIR) sequence and diffusion-weighted imaging technique with single-shot echo-planar spin-echo sequence. The transcatheter closure of ASD was performed by three expert interventional cardiologists. Amplatzer septal occluder device was implemented for the closure of the defect. No contrast medium was administered in the course of the procedure.RESULTSNone of the patients had diffusion restricted cerebral lesions resembling microembolic infarctions on postprocedural MRI. Preprocedural MRI of two patients revealed nonspecific hyperintense white matter lesions on FLAIR images with increased diffusion, which were considered to be older ischemic lesions associated with previously occurred paradoxical embolism.CONCLUSIONThe current study suggests that percutaneous closure of the ASD, when performed by experienced hands, may be free of cerebral microembolization in pediatric patients. However, due to the relatively small sample size, further studies with larger patient groups are needed for the validation of our preliminary results.